2014
DOI: 10.17511/ijpr.2014.i01.04
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Neurodevelopmental and Etiological profile of children with Cerebral Palsy

Abstract: Background: Clinical spectrum of cerebral palsy (CP) is different in developing and developed countries. We evaluated the clinical profile, etiological factors and co-morbidities of children with CP in central India. Methods: 50 children with CP came to the hospital in our rehabilitation center were compared with our previous study done in India and western countries. Results: Spastic quadriplegia is the commonest type of CP (90%). Birth asphyxia remains the main (48%) etiological factor. Prematurity was secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The majority of our participants (95.4%) were underweight, This percent is, higher than saudia Arabia study by Almuneef et al, [13] as only 41.3% children with CP were underweight. also higher than those reported in Uganda (42%) Silva et al, [14] , Greece (38.1%) Karagiozoglou-Lampoudi et al, [15] .…”
Section: Discussioncontrasting
confidence: 55%
“…The majority of our participants (95.4%) were underweight, This percent is, higher than saudia Arabia study by Almuneef et al, [13] as only 41.3% children with CP were underweight. also higher than those reported in Uganda (42%) Silva et al, [14] , Greece (38.1%) Karagiozoglou-Lampoudi et al, [15] .…”
Section: Discussioncontrasting
confidence: 55%
“…described probable etiological factors of CP children in Central India and found that antepartum hemorrhage and hypertension contributed 10% and 6%, respectively. [ 9 ] Pattar and Yelamali described similar results with equal frequency of maternal anemia, PIH/toxemia, and APH (in 6% cases each) as risk factors of CP. [ 10 ]…”
Section: Discussionmentioning
confidence: 81%
“…The male: female ratio varied from 1.2:1 to 3.16:1 in various studies. [6][7][8][9] Most common age of presentation to the hospital was between 1-3 years. 59(60.82%) of the patients of age group 1-3 years came for specific treatment to this hospital.…”
Section: Discussionmentioning
confidence: 99%